Mitochondrial Quality Control in Cardiac Diseases - Campos, Juliane C.; Bozi, Luiz H. M.; Bechara, Luiz R. G.; Lima, Vanessa M.; Ferreira, Julio C. B. (Frontiers in Physiology, 2016)
Disruption of mitochondrial homeostasis is a hallmark of cardiac diseases. Therefore, maintenance of mitochondrial integrity through different surveillance mechanisms is critical for cardiomyocyte survival. In this review, we discuss the most recent findings on the central role of mitochondrial quality control processes including regulation of mitochondrial redox balance, aldehyde metabolism, proteostasis, dynamics and clearance in cardiac diseases, highlighting their potential as therapeutic targets.